Optimization of e-document workflow for order calculation - Nechepurenko, Dmytro (Technology audit and production reserves, 2018)
The object of research is automated control systems at enterprises of the machine-building industry. One of the most problematic places is the calculation of the cost of an order in the presence of a large number of orders of various types, which is typical for modern enterprises. In the course of the research, an analysis of the systems for calculating the cost of an order is carried out and the features of the formation of the order are determined at machine-building enterprises. Ways of optimization of electronic document circulation by application of the concept of use of the automated calculation of cost of the order on the basis of formation of the data on separate production units or sets are offered. The concept of calculating the cost of using each production unit for manufacturing the order provides a flexible tool for the management of the company. This allows to create an unlimited number and variety of models of technological units in an automated control system, to supplement and improve parameters for a more accurate determination of the cost of production. To do this, use directories of operations that contain information about the necessary equipment, tools, supplies, the necessary skills of workers to fulfill the order, the cost of their work and the like. The next step is the modernization of the order generation algorithm, requiring the introduction of changes in the automated enterprise management system. The proposed concept of using automated calculation of the cost of an order based on the formation of data for individual production units or sets allows to significantly reduce the cost of maintaining the planning and economic department. When ordering documentation, an analysis of available consumables is conducted, the necessary information is sent to the procurement department, the necessary equipment is selected taking into account the loading of individual devices in a certain period of time. Also, the processing time for orders and the submission of commercial offers is reduced. This opens up new opportunities for the company to participate in tender proposals and to identify the optimal variant of the offer, instantly calculating several quality-price options for manufacturing products.